a-Tocopherol, ascorbic acid and carotenoid content in Centella asiatica leaf tissue and callus cultures. - Kusnan, Misri; Jali, Azman; Mahmood, Maziah; Yusuf, Norhayati; Mohd Fadzillah, Nor'Aini (Universiti Putra Malaysia Press, 2011)
Green leafy vegetables constitute a major part of balanced diet and are good sources of minerals and vitamins. These beneficial effects are attributed to the presence of antioxidants. Antioxidants also contribute to the defence mechanisms against oxidative stress. Centella asiatica, which is locally known as â€˜pegaga,â€™ is claimed to be rich in natural antioxidative compounds. This study was conducted to determine the amount of ascorbic acid, α-tocopherol and carotenoid content in twelve accessions of C. asiatica (CA01 to CA12-comprises of â€˜pegaga nyonyaâ€™, â€˜pegaga kampungâ€™ and â€˜pegaga saladâ€™) leaf tissues and callus cultures. The antioxidative constituents of C. asiatica in the leaf tissues and cultures were found to vary significantly between the accessions. In particular, CA03 leaves (â€˜pegaga saladâ€™) exhibited the highest concentrations of ascorbic acid (95.86 ± 12.60 µg/g.fwt), whereas CA10 (â€˜pegaga nyonyaâ€™) produced the highest concentration of α-tocopherol (0.233 ± 0.029 µg/g.fwt) and carotenoids (36.55 ± 0.06 µg/g.fwt). The antioxidants studied were also successfully detected in the cultures of C. asiatica, with CA08 callus (â€˜pegaga kampungâ€™) being dominant in ascorbic acid (167.21 ± 5.30 µg/g.fwt) and a-tocopherol (5.72 ± 0.29 µg/g.fwt), whereas CA12 callus (â€˜pegaga kampungâ€™) had the highest carotenoid content (1.04 ± 0.07 µg/g.fwt). Meanwhile, the amount of non-enzymatic antioxidants (except for carotenoid content) was significantly higher in the cell cultures compared to the leaf tissues. The results indicated that CA03 and CA10 leaf tissues, as well as CA08 and CA12 calli were good sources of natural antioxidants compared to other accessions.